Review of Studies on Glacier Lake Outburst Floods and Associated Vulnerability in the Himalayas - Ghimire, Motilal (Himalayan Review, 2009)
The present study is based on the reviews of the available scientific research publications and reports on Glacier Lake Outburst Floods events in Nepal and Bhutan. The study explores the nature, causes, occurrence, and impact of GLOF events and assesses the associated vulnerability, and the existing adaptation measures taken in these countries. Recently, these events have become a serious threat to socio-economy and infrastructures in downstream of the snow fed rivers. A few commendable studies indicate glacier retreat, a possible cause of GLOF; but these studies are confined to certain regions and are based on short observations, limited temporal data on hydro-meteorology and the indirect evidences. Therefore, it is still early to make firm conclusions about the state of affairs. However, these studies have made the government and the community aware of the risk of GLOFs, implicated glacier retreat, climate change, and to look for better adaptation measures. Key words: Glacier Lake; Outburst; flood; GLOF hydrology; Moraines; Glacier retreat; Global Warming; Climate change; Vulnerability; Adaptation. The Himalayan Review 35-36 (2004-2005) 49-64